2001
DOI: 10.1038/sj.onc.1204707
|View full text |Cite
|
Sign up to set email alerts
|

G2 phase cell cycle arrest in human skin following UV irradiation

Abstract: The contribution of the short wavelength ultraviolet (UV) component of sunlight to the aetiology of skin cancer has been widely acknowledged, although its direct contribution to tumour initiation or progression is still poorly understood. The loss of normal cell cycle controls, particularly checkpoint controls, are a common feature of cancer. UV radiation causes both G1 and G2 phase checkpoint arrest in vitro cultured cells. In this study we have investigated the cell cycle responses to suberythemal doses of U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
64
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 34 publications
13
64
0
1
Order By: Relevance
“…Interestingly, Gadd45 can be upregulated by UV exposure in a p53-independent fashion through the transcriptional factors Oct-1 and NF-YA (Jin et al, 2000;Takahashi et al, 2001). p53-independent G2 arrest in response to UV also involves a p38 kinase-mediated block in the activation of the mitotic Cdk complexes by cdc25 (Herzinger et al, 1995;Gabrielli et al 1997;Bulavin et al, 2001;Pavey et al, 2001). Recent studies making use of short-term, whole-organ skin cultures have confirmed that basal and suprabasal layer melanocytes and keratinocytes undergo G2 cell cycle arrest in response to suberythemal doses of UV radiation (Pavey et al, 2001).…”
Section: Uv-mediated Cell Cycle Arrest and Re-entrymentioning
confidence: 93%
See 2 more Smart Citations
“…Interestingly, Gadd45 can be upregulated by UV exposure in a p53-independent fashion through the transcriptional factors Oct-1 and NF-YA (Jin et al, 2000;Takahashi et al, 2001). p53-independent G2 arrest in response to UV also involves a p38 kinase-mediated block in the activation of the mitotic Cdk complexes by cdc25 (Herzinger et al, 1995;Gabrielli et al 1997;Bulavin et al, 2001;Pavey et al, 2001). Recent studies making use of short-term, whole-organ skin cultures have confirmed that basal and suprabasal layer melanocytes and keratinocytes undergo G2 cell cycle arrest in response to suberythemal doses of UV radiation (Pavey et al, 2001).…”
Section: Uv-mediated Cell Cycle Arrest and Re-entrymentioning
confidence: 93%
“…However, there are conflicting data on the effect of a-MSH on the growth of melanocytic cells, which may be relevant only to cells in culture (see the review by Thody, 1999). Moreover, UVB is known to induce expression of the cell cycle inhibitor p16INK4a (Pavey et al, 2001), an effect that is potentiated by a-MSH (Pavey and Gabrielli, 2002). An exciting and largely unexplored area of research concerns the stimulation of melanocytes through UVmediated upregulation of growth factors, such as endothelin-1 and bFGF, originating from nonmelanocyte cell types (Archambault et al, 1995;Tada et al, 1998).…”
Section: Uv-induced Proliferation and The Role Of Growth Factor Recepmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of nuclear p16 to the G 2 phase arrest is unclear, but studies using in vitro cultured cells have previously demonstrated that p16 inhibits cdk4/cyclin-D activity in the late S/early G 2 phase, which apparently is required for G 2 phase progression. Alternatively, p16 may have a role in constituting a G 1 phase arrest after G 2 arrest (Gabrielli et al, 1999;Pavey et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…While it may simply reflect an increased mutational burden that would lead to a higher probability of accumulating sufficient additional mutations required for cancer to develop, it is interesting to contemplate whether a more direct mechanism may also play a role since UVR has been shown to induce p16 expression in human skin (Pavey et al, 1999), where it is involved in a UVRinduced G2 phase cell-cycle block (Pavey et al, 2001). Additionally, there is a tantalizing but not fully understood link to MC1R, since a-MSH has been shown to potentiate p16 expression in human skin after UVR treatment (Pavey et al, 2002).…”
Section: Uvrmentioning
confidence: 99%